Development of masonry mortar with discarded sururu shells from the Mundaú-Manguaba lagoon estuary complex, Brazil - Renato Carvalho Menezes; Sheyla Karolina Justino Marques; Ronny Francisco Marques de Souza (Cleaner Engineering and Technology, 2022)
Located in the state of Alagoas in Brazil, the Mundaú-Manguaba lagoon estuary complex - MMLEC 2 has great socioeconomic importance, since in all its extension; there is reproduction of fish, crustaceans and mollusks, which guarantee income for fishermen and shellfish catchers in the region. Among mollusks, sururu (Mytella falcata) is among the most important due to its value in the Alagoas cuisine. After caught, these mollusks are cooked and removed from their shells, which are usually discarded in vacant lots, public roads and even at the banks of lagoons, generating several environmental impacts. Studies with shells of bivalve mollusks indicate that they are basically composed of calcium carbonate, chemical substance used on a large scale in various branches and industrial activities. The aim of this study was to evaluate the technical feasibility of producing masonry mortar with the incorporation of sururu shell in partial sand substitution. Specimens were produced in the following substitution percentages: 0% 10%, 20%, 30%, 40% and 50%. Subsequently, mechanical compressive strength, water absorption, consistency index and Scanning Electron Microscopy - SEM tests were performed. It was observed that the incorporation of sururu shell in the mortar resulted in decrease in the mechanical compressive strength and increase in consistency and water absorption. The results indicated that all the mortars produced presented mechanical resistance to compression above the minimum predicted for this use, however, a correction of water dosage must be carried out during the preparation of the mortars to adapt to the standardized consistency index. In relation to the capillary water absorption test, the mortars with substitution of up to 20%, presented coefficients of water absorption similar to the conventional mortar. Therefore, the mortar developed in this research is an important alternative to the environmental imbalance of the sururu production chain in the Mundaú-Manguaba lagoon estuary complex - MMLEC.